Impact of Pseudomonas aeruginosa, white fungus waste, and nano fertilizer on pyrophosphatase activity, growth characteristics, and yield of stevia plant - Al-budairy, Zahraa J. (2025)
Aimed to know the effect of Pseudomonas aeruginosa bacteria, white fungus waste, and nano fertilizer on the pyrophosphatase enzyme, growth characteristics, and yield of stevia plants. The bacterial vaccine represented the first factor. It was added at two levels: B0 (without inoculum) and B1 (injecting 2 ml of liquid bio-inoculum represented by P. aeruginosa). The second factor was adding white fungus waste at three levels defined by Ab0 (without adding white mushroom waste), Ab1 (adding white mushroom waste at level 5 tons/h), and Ab2 (adding white mushroom waste at level 10 tons/h). Nano fertilizer was added as a third factor at four levels: N0 (without adding nano fertilizer), N1 (adding 4 kg/h of nano zinc), N2 (adding 2 kg/h of nano boron), and N3 (adding a mixture of 1 kg/h of nano boron + 2 kg/h of nano zinc). The triple combination B1Ab1N3 achieved a significant superiority in the activity of the pyrophosphatase enzyme in the first and second harvests and recorded (260.67 and 166.00) µg PO4-3-P/g soil 5/h, respectively, compared to the treatment without addition, which recorded (55.00 and 44.67) µg PO4-3-P/g soil 5/h, respectively. In contrast, the triple combination B1Ab2N3 achieved the highest growth and yield characteristics of the stevia plant and recorded the highest rate of plant height, dry weight of leaves and total yield, and recorded 83.90 and 76.00 cm/plant, 61.7 and 53.0 g/plant, 4933 and 4240 kg/h, respectively, compared to the treatment without addition, which recorded 68.98 and 60.63 cm/plant, 44.6 and 38.1 g/plant, 3563 and 3050 kg/h respectively.